Efektivitas Pelaksanaan Sistem Pemerintahan Berbasis Elektronik (SPBE) dalam Peningkatan Kualitas Layanan Publik di Pemerintahan Kota Bekasi - Ersya Alifia Kharisma Islami; Hananto Widodo (CV Rewang Rencang, 2025)
The implementation of the Electronic-Based Government System (SPBE) aims to enhance efficiency, transparency, and the overall quality of public services. In Bekasi City, SPBE has shown positive results, particularly in accelerating service processes, improving accessibility, increasing data accuracy, and strengthening information transparency. However, several challenges persist, including low digital literacy among citizens, limited capacity of government personnel, and uneven technological infrastructure. This study concludes that while SPBE has significant potential to strengthen public administration, its effectiveness requires continuous improvement in human resources, infrastructure development, and broader public outreach to ensure optimal and sustainable implementation.